PUMA Cooperates with p21 to Regulate Mammary Epithelial Morphogenesis and Epithelial-To-Mesenchymal Transition. - Yanhong Zhang; Wensheng Yan; Yong Sam Jung; Xinbin Chen (PLoS ONE, 2013)
Lumen formation is essential for mammary morphogenesis and requires proliferative suppression and apoptotic clearance of the inner cells within developing acini. Previously, we showed that knockdown of p53 or p73 leads to aberrant mammary acinus formation accompanied with decreased expression of p53 family targets PUMA and p21, suggesting that PUMA, an inducer of apoptosis, and p21, an inducer of cell cycle arrest, directly regulate mammary morphogenesis. To address this, we generated multiple MCF10A cell lines in which PUMA, p21, or both were stably knocked down. We found that morphogenesis of MCF10A cells was altered modestly by knockdown of either PUMA or p21 alone but markedly by knockdown of both PUMA and p21. Moreover, we found that knockdown of PUMA and p21 leads to loss of E-cadherin expression along with increased expression of epithelial-to-mesenchymal transition (EMT) markers. Interestingly, we found that knockdown of ΔNp73, which antagonizes the ability of wide-type p53 and TA isoform of p73 to regulate PUMA and p21, mitigates the abnormal morphogenesis and EMT induced by knockdown of PUMA or p21. Together, our data suggest that PUMA cooperates with p21 to regulate normal acinus formation and EMT.